Keputusan konsumen menggunakan online delivery service: faktor budaya, faktor sosial, faktor psikologis, dan faktor pribadi sebagai variabel determinan - Juwita, Tri Analia; Puspita Sari, Juli Dwina (JIM: Jurnal Ilmiah Mahasiswa, 2024)
This research aimed to analyze the impact of cultural, social, personal, and psychological factors on consumer decisions to use delivery services in Langsa City, both individually and collectively. A quantitative approach was employed, gathering primary data by distributing questionnaires to 100 consumers who had used delivery services in Langsa City. Initial data collection also included interviews with a few delivery service users in Langsa City, along with observation and documentation. The analytical method used was multiple linear regression, beginning with classical assumption tests and followed by hypothesis testing. Hypotheses were tested using statistical methods, specifically the t-test (for individual analysis) and the F-test (for collective analysis). The results showed that, while cultural and social factors had a positive but not significant effect on consumer decisions to use delivery services in Langsa City, personal and psychological factors had a positive and significant impact. Collectively, cultural, social, personal, and psychological factors influenced consumer decisions to use delivery services in Langsa City.